Chitosan-Based Delivery of Avian Reovirus Fusogenic Protein p10 Gene: In Vitro and in Vivo Studies Towards a New Vaccine Against Melanoma - Garcia Huidobro-Toro, J; Spencer-Ossa, E; Castillo-Nara, A; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Milla-Brito, L; Cortez-San Martin, M; Robles-Planells, C; Rojo-Castillo, L; Matiacevich, S; Barrera-Ávalos, C (Hindawi Limited, 2020)
Reovirus is known to have an anticancer effect in both the preclinical and clinical assays. Current evidence suggests that the reovirus-mediated impact on tumor growth depends on the activation of specific antitumor immune responses. A feasible explanation for the oncolytic effects and immune system activation is through the expression of the fusogenic reovirus protein. In this work, we evaluated the in vivo antitumor effects of the expression of fusogenic protein p10 of avian reovirus (ARV-p10). We used chitosan nanoparticles (CH-NPs) as a vehicle for the ARV-p10 DNA in murine B16 melanoma models both in vitro and in vivo. We confirmed that ARV-p10 delivery through a chitosan-based formulation (ARV-p10 CH-NPs) was capable of inducing cell fusion in cultured melanoma cells, showing a mild cytotoxic effect. Interestingly, intratumor injection of ARV-p10 CH-NPs delayed tumor growth, without changing lymphoid populations in the tumor tissue and spleen. The injection of chitosan nanoparticles (CH-NPs) also delayed tumor growth, suggesting the nanoparticle itself would attack tumor cells. In conclusion, we proved that in vitro ARV-p10 protein expression using CH-NPs in murine melanoma cells induces a cytotoxic effect associated with its cell fusion. Further studies are necessary for establishing a protocol for efficient in vivo DNA delivery of fusion proteins to produce an antitumoral effect. © 2020 Claudia Robles-Planells et al.